2018
DOI: 10.13083/reveng.v26i1.852
|View full text |Cite
|
Sign up to set email alerts
|

Otimização Energética De Um Trator Agrícola Utilizando Normas Técnicas Em Operações De Gradagem

Abstract: A operação de gradagem é uma técnica bastante utilizada no preparo do solo, devido ao rendimento operacional e à otimização do consumo de combustível durante a atividade, a mesma gera redução nos custos operacionais. Este trabalho teve por objetivo a otimização energética de um trator agrícola, utilizando normas técnicas em operações de gradagem. O experimento foi realizado na área experimental da Fazenda Lageado da Faculdade de Ciências Agronômicas – FCA da Universidade Estadual Paulista - UNESP, localizada n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 2 publications
3
9
0
6
Order By: Relevance
“…Similar results were obtained by Estrada et al (2016) when evaluating the performance of a diesel engine using different hydrated ethanol mixtures. Martins et al (2018) measured the energy performance of an agricultural tractor using an offset disk harrow and found no significant differences in DF, corroborating the present study. Tabile et al (2009) evaluated fuel consumption with different castor bean biodiesel mixtures and found that SFC was 358 g kW h -1 and DF was 23 kN, which are similar to the results of the present study.…”
Section: Resultssupporting
confidence: 89%
“…Similar results were obtained by Estrada et al (2016) when evaluating the performance of a diesel engine using different hydrated ethanol mixtures. Martins et al (2018) measured the energy performance of an agricultural tractor using an offset disk harrow and found no significant differences in DF, corroborating the present study. Tabile et al (2009) evaluated fuel consumption with different castor bean biodiesel mixtures and found that SFC was 358 g kW h -1 and DF was 23 kN, which are similar to the results of the present study.…”
Section: Resultssupporting
confidence: 89%
“…Engenharia Agrícola,Jaboticabal,v.40,n.5 The parameters HFC, OS, DBP, DBE, and EL increased as the used gear increased, whereas the parameter ES showed the opposite behavior. Martins et al (2018) analyzed the energy optimization of agricultural tractors and found similar results to the parameters OS, DBP, and DBE. The high number of the selected gear provided a higher effective speed and, therefore, higher OS, DBP, DBE, and EL and hence higher HFC, reducing ES.…”
Section: Resultsmentioning
confidence: 72%
“…A utilização da mecanização agrícola tornou mais eficiente diversas operações, sendo o trator a principal máquina utilizada na realização das atividades agrícolas permitindo assim a realização de práticas de cultivo mais eficientes (Martins et al, 2018). Conforme (Pinto et al, 2020) o trator é uma máquina auto propelida que permite a realização de práticas de cultivo mais eficientes, dentro do período considerado ótimo para as culturas.…”
Section: Introductionunclassified